How do you work this math problem out? i know the answer but not how to get it.?

given f(x)=4x+1 and g(x)=x^2-2, which of the following is an expression for f(g(x))

the answer is 4x^2-7 but how do i get this? ten points for best answer.

1 Answer

  • 1 decade ago
    Favorite Answer

    In f(g(x)), you replace g(x) with x^2-2, since g(x) is x^2-2.

    So f(x^2-2) = 4(x^2-2)+1

    f(x^2-2) = 4x^2-8+1

    f(x^2-2) = 4x^2-7 or f(g(x)) = 4x^2-7.

Still have questions? Get your answers by asking now.